HEALTH RISKS OF CLEAN WATER SUPPLY CONDITIONS AFTER EARTHQUAKE DISASTER (CASE STUDY : WANGUNJAYA VILLAGE, CIANJUR REGENCY - Nurrachmi, Fauzia
Earthquakes can cause damage to water and sanitation infrastructure and even impact public health. The clean water piping system that has been provided by the Institute for Research and Community Service (LPPM) ITB in the aftermath of the earthquake disaster in Wangunjaya Village Cianjur Regency, needs to be evaluated for health risks related to the provision of clean water after the earthquake disaster. The membrane filter method and observation of environmental infrastructure were conducted to determine the condition of clean water supply and sanitation. Data analysis used Spearman correlation and QMRA. The results of water source tests in areas that received ITB piping assistance did not generally find Total Coliform and E. coli contamination that exceeds the quality standards of Minister of Health Regulation No. 2 of 2023. A total of 68% have latrine facilities but do not have a fecal distribution or treatment system. There was a significant correlation between the variable well depth (p-value = 0.001) with Total Coliform contamination, a distance of latrine facilities (p-value=0.009 and 0.049) with E.coli, and Total Coliform contamination. Quantitative microbial risk assessment showed that there is an annual infection probability of Pinf, which is higher than the risk level for E.coli < 10-4 . This study is expected to provide an overview of the condition of water supply, sanitation, and public health risks related to the bacteriological quality of water that can affect the success of water supply after the earthquake disaster.